Brazilian native passion fruit (Passiflora tenuifila Killip) is a rich source of proanthocyanidins, carotenoids, and dietary fiber. (September 2021) - Santos, José Thiago do Carmo; Petry, Fabiane Cristina; Tobaruela, Eric de Castro; Mercadante, Adriana Zerlotti; Gloria, Maria Beatriz Abreu; Costa, Ana Maria; Lajolo, Franco Maria; Hassimotto, Neuza Mariko Aymoto
Graphical abstract: Highlights: Proanthocyanidins and carotenoids were evaluated for the first time in P. tenuifila. Fruits presents high contents of phenolic compounds and elevated antioxidant potential. P. tenuifila fruits are a good source of dietary fiber. Both ripening stages provides similar flavonoids profiles and proximate composition. Abstract: Passiflora tenuifila is a Brazilian native passion fruit consumed by the local population and is a dietary source of bioactive compounds with potential biological activity. The aim of this study is to evaluate the nutritional value of P. tenuifila fruit and its bioactive compounds at two ripening stages. Three batches of fruit were collected at mature-green and ripe stages, and phenolic compounds, carotenoids, and polyamines were analyzed by HPLC-DAD and LC-MS/MS. The fruit is a good source of dietary fiber. Proanthocyanidin dimers are the major phenolic compounds (up to 84%) at both stages, followed by the C-glycosylated luteolin. Lutein and β-carotene are the major carotenoids, contributing up to 50% of total carotenoids. The OPLS-DA segregates the mature-green and ripe fruits, as carotenoids are responsible for this separation. In conclusion, passion fruit can be consumed at both stages of maturation without losses of bioactive compound contents or nutritional value.